(untitled) (Journal of Economic Research & Business Administration, 2015)
Prospects for development of personnel management in the system of modern enterprise policy in Kazakhstan suggest that in the selection of candidates could be a form of “Self-identity”, using practical assignments, temporary replacement positions, internships and the like should be supported by the interchangeability of schedules and vacations for employees, taking into account the plans and programs. They will help reduce the cost of recruitment and get more targeted and effective recruitment.